Genetic and non-genetic factors affecting pre-weaning relative growth rate (RGR) in Black Bengal and its halfbred kids - SINGH, D K; KUMAR, SAROJ; SINGH, N S; SINGH, C S P (The Indian Journal of Animal Sciences, 2014)
The present study was conducted on 817 (200, Black Bengal; 414, Jamunapari x Black Bengal and 203, Beetal x Black Bengal) kids of 53 sires born during 198.1-86 under the All India Co-ordinated Research Project on Goat at Ranchi Veterinary College, Ranchi(Jharkhand).Relative growth rate (RGR) in body weight was studied during 0-4,4-8,8-12 and 0-12 weeks of age. The variation in RGR in body weight during 0-4 weeks of age due to genetic group, year of birth, season of birth, type of birth, birth weight and dams' weight at kidding was significant. While RGR during 4-8 weeks of age varied significantly due to year of birth, season of birth, generation and birth weight. During 8-12 weeks of age, the effect of year of birth and dams' weight at kidding on RGR in body weight was significant. However, during 0-12 weeks, it varied significantly due to genetic group, generation, year of birth, season of birth, type of birth and birth weight. The random effect of sire on RGR in body weight was not significant. Heritability estimate of RGR in pre-weaning body weight (0.053Â± 0.067) was low. The RGR in 0 - 4 weeks had positive and significant phenotypic (0.688) association with RGR during 0 - 12 weeks of age. .